Neural responses to dynamic adaptation reveal the dissociation between the processing of the shape of contours and textures. (June 2020) - Wright, Damien; Dering, Benjamin; Martinovic, Jasna; Gheorghiu, Elena
Abstract: Shape-adaptation studies show that surround textures can inhibit the processing of contours. Using event-related potentials (ERP), we examined the time-course of neural processes involved in contour-shape and texture-shape processing following adaptation to contours and textures. Contours were made of Gabor strings whose orientations were either tangential or orthogonal to the contour path, while textures were made of a series of contours arranged in parallel. We focused on two ERP components – P1, related to low-level visual processes and N1, broadly indicative of mid-level vision– and, on ERP difference waves (no-adaptor minus with-adaptor) to isolate the effects of adaptation, which are fundamentally distinct from individual processes driving P1 and N1 components. We found that in the absence of adaptation, the N1 component for contour-tests peaked later and increased in amplitude compared to the N1 for texture-tests. Following adaptation, the ERP difference wave for contour-tests revealed an early and a late component that were differentially affected by the presence of surround texture, but critically not by its orientation. For texture-tests, the early component was of opposite polarity for contours compared to texture adaptors. From the temporal sequence of ERP modulations, we conclude that texture processing begins before contour processing and encompasses the stages of perceptual processing reflected in both the low-level P1 and the mid-level N1 vision-related components. Our study provides novel evidence on the nature of separable and temporally distinct texture and contour processing mechanisms, shown in two difference wave components, that highlights the multi-faceted nature of dynamic adaptation to shape when presented in isolation and in context.